(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In India, body image research is still in its infancy, and the social and psychological effects of having a negative body image are not given enough attention. The purpose of the current study is to learn about a person's body image and how it relates to social and psychological outcomes. The current study focuses on how boys and girls think about their bodies, idealised physical characteristics, factors that affect body image, and the effects of having a good or bad body image. The results of this study show that the significance of body image in Indian culture is comparable to that of body image in Western culture. Comparable concepts in the east and west could be explained by the digital environment. Today's digital environment has made borders more permeable due to communication. Sending messages from one nation to another is now simple. A variety of media are available to aid in understanding another civilization's culture and way of life. One such means of message transmission that works well is the media. The second source of a comparable understanding of body image could be the introduction of liberalisation, privatisation, and globalisation. Any company in the world is welcome to sell its goods in the Indian market. In order to promote their products, these businesses frequently flaunt their style and way of life. Third, similar body image concepts may have been caused by exposure to fashion publications, reading fashion articles, and imitating and blindly adhering to the western lifestyle, whether it be in food or fashion. In this case, it is possible to assert that a particular culture has lost some of its distinctiveness.